Assessment of natural radionuclides in the soil samples from Marwar region of Rajasthan, India. (July 2015) - Rani, Asha; Mittal, Sudhir; Mehra, Rohit; Ramola, R C
Abstract: In the present investigation, 226 Ra, 232 Th and 40 K analysis has been carried out in the soil samples collected from different locations of Jodhpur and Nagaur districts of Northern Rajasthan, India using gamma ray spectroscopy. The measured activity concentration ranges from 13±8 to 36±9 Bq kg −1, 40±9 to 71±11 Bq kg −1 and 294±125 to 781±159 Bq kg −1 with the mean value of 24±9 Bq kg −1, 55±11 Bq kg −1 and 549±141 Bq kg −1 for 226 Ra, 232 Th and 40 K, respectively. The radium equivalent activity of all the soil samples ranges from 114 to 157 Bq kg −1 with an average value of 141 Bq kg −1, which is lower than the safe limit 370 Bq kg −1 as set by the Organization for Economic Cooperation and Development. The total absorbed dose of all the investigated samples varies from 56 to 77 nGy h −1 with an average value of 68 nGy h −1 . The overall annual effective dose ranges from 0.34 to 0.47 mSv with the average value of 0.41 mSv. The corresponding values of external and internal hazard index of all the soil samples ranges from 0.32 to 0.43 and 0.37 to 0.53 with an average value of 0.39 and 0.45 respectively. It was observed that the soil of Jodhpur and Nagaur districts is suitable for construction purpose without posing any health hazard. Highlights: Natural radionuclides were studied in soil samples of Jodhpur and Nagaur districts. All the samples were characterized by using NaI(Tl) Gamma ray spectrometry. External and internal hazard for the studied soil samples were within safe limit. The soil of studied area can be used as a construction material.